Peran Dinas Hukum Tni Au Terhadap Prajurit DalamPendampingan Kasus Pidana Militer(Studi Kasus Lanud Adi Soemarmo Surakarta)Disusun - Ningsih, Anjung Setya Widya; , Dr. Natangsa Surbakti, S.H., M.Hum; , Hartanto, S.H., M.Hum (2016)
Indonesia is a country which based on the law, there are three basics of principles of the state laws which are: the rule of law,the equation in front of the law, and the law enforcement. The equation in front of the law for everyone should be based on the equation treatment (equal treatment) for everyone, get treatmentby the judge (audi et alterampartem) and give a guarantee the access to obtain justice (acces tho justice) for everyone regardless of the background. Justice should be given by the state to everyone, and the law has a duty to keep it for all without exception as well as the soldiers military. For the sake of a defense case faced by the the suspects or the defendants that are the soldiers military also entitled to get the legal aid against the soldiers military given tho achieve justice and equality in front of the law.